2010
DOI: 10.2337/db09-0138
|View full text |Cite
|
Sign up to set email alerts
|

Increased Brain Fatty Acid Uptake in Metabolic Syndrome

Abstract: OBJECTIVETo test whether brain fatty acid uptake is enhanced in obese subjects with metabolic syndrome (MS) and whether weight reduction modifies it.RESEARCH DESIGN AND METHODSWe measured brain fatty acid uptake in a group of 23 patients with MS and 7 age-matched healthy control subjects during fasting conditions using positron emission tomography (PET) with [11C]-palmitate and [18F]fluoro-6-thia-heptadecanoic acid ([18F]-FTHA). Sixteen MS subjects were restudied after 6 weeks of very low calorie diet interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(156 citation statements)
references
References 27 publications
3
137
1
3
Order By: Relevance
“…Although the reason for this difference is unknown, this could be related to a lower number of astrocytes in cortical versus hypothalamic areas (52) and/or differences in the expression of proteins and enzymes involved in LCFA metabolism (LCFA transporters, acyl-CoA synthase, and CPT-1) that may affect LCFA uptake. Nonetheless, our results are consistent with previous reports showing regional differences in palmitate oxidation and incorporation in rat (51,53) or human brain (54) and high levels of palmitate incorporation in the arcuate nucleus compared with non-hypothalamic areas (53) after systemic administration of radiolabeled palmitate tracers. In addition, in agreement with the former study in vivo (53), we found here that palmitate oxidation rate in MBH and cortical slices was proportional to the rate of glucose utilization.…”
Section: Discussionsupporting
confidence: 83%
“…Although the reason for this difference is unknown, this could be related to a lower number of astrocytes in cortical versus hypothalamic areas (52) and/or differences in the expression of proteins and enzymes involved in LCFA metabolism (LCFA transporters, acyl-CoA synthase, and CPT-1) that may affect LCFA uptake. Nonetheless, our results are consistent with previous reports showing regional differences in palmitate oxidation and incorporation in rat (51,53) or human brain (54) and high levels of palmitate incorporation in the arcuate nucleus compared with non-hypothalamic areas (53) after systemic administration of radiolabeled palmitate tracers. In addition, in agreement with the former study in vivo (53), we found here that palmitate oxidation rate in MBH and cortical slices was proportional to the rate of glucose utilization.…”
Section: Discussionsupporting
confidence: 83%
“…Recently, however, the uptake of fatty acids by the brain has been demonstrated using stable isotopes and positron emission tomography and was found to be increased in individuals with the metabolic syndrome and to subsequently decline after weight loss (114) . Apart from the use of lipids as an energy source in the brain it has become increasingly apparent that lipids and lipid metabolism play an important role in the regulation of energy balance by the hypothalamus.…”
Section: Hypothalamic Fatty Acid Metabolismmentioning
confidence: 99%
“…In particular, the concentration of palmitate almost doubled as compared to control, above 1100 g/L in the CSF of traumatic brain injury versus around 600 g/L in control (Pilitsis et al, 2003;Pilitsis et al, 2001;Zamir et al, 1991). FFAs in plasma can cross the blood-brain barrier (Dhopeshwarkar and Mead, 1973;Smith and Nagura, 2001), and high fat diets increase the uptake of fatty acids by the brain from the plasma (Karmi et al, 2010;Wang et al, 1994). The concentration of FFAs in normal human plasma in vivo generally ranges between 0.3-1.0mM (Dole, 1956;Shultz, 1991;Tikanoja et al, 1989).…”
Section: Discussionmentioning
confidence: 99%